A influência da política monetária no desempenho do Ebitda das empresas: uma pesquisa com empresas listadas na Bolsa de Valores de SP (2009-2015) - Silva, Luís Gustavo Dias da (2016)
Since Brazil independence in 1822, it has always suffered from high indebtedness and periods of inflation and hyperinflation which after successive economic stabilization plans, has made the economy increasingly gloomy for companies in general. Only in 1994, with the Real Plan, the Brazilian economy has balanced with adequate inflation for developing countries. However, external shocks came with the Mexican, Asian and Russian financial crises. After five years of stabilization of inflation, in 1999, Brazil was obliged to abandon one of the pillars of support of the Real Plan: the exchange anchor. Thus, with the adoption of the macroeconomic tripod of "Inflation Targets", "Primary Surplus" and "Floating Exchange", Brazil has resumed GDP growth and controls inflation. At this moment, the Monetary Policy (Contractionary or Expansionist) has gained important role, mainly when the federal government has started to use the SELIC rate as basic interest parameter of the Brazilian economy and one of the strong formal instruments of control of inflation. The objective of this research has known (i) there are influence of Monetary Policy on the EBITDA’s performance of the companies listed on the São Paulo Stock Exchange and (ii) how long after the increase or decrease the SELIC Rate (Brazilian Monetary Policy), there is an impact on companies’ EBITDA. This research has been motivated by the relevance and timeliness of that topics because the SELIC rate to control the rise in inflation for reasons exogenous to the companies in general, has influenced the endogenous performance of these same companies, affecting one of the most important economic-financial-accounting: the EBITDA. The methodology has used, which included the development of a statistical and macroeconomic model own, has been regression in the data panel, with a detailed analysis of the 17 segments of companies in which the 314 companies surveyed have distributed. The results have indicated that there is influence of the Monetary Policy in the EBITDA of some sectors of companies with a three-month and a nine-month time span predominance, with relevant statistical significance. It has concluded that the unique and different moments in which the Monetary Policy is used by the monetary authority has influenced the operational performance of the companies, translated by the accounting-financial managerial indicator called EBITDA